Polymerase chain reaction evidence for human immunodeficiency virus 1 neutralization by passive immunization in patients with AIDS and AIDS-related complex. - Karpas, A (1990)
We tried to assess the long-term safety and potential efficacy of passive immunization in AIDS-related-complex (ARC) and AIDS patients. We also wanted to establish whether hyperimmune plasma from healthy human immunodeficiency virus 1 (HIV-1)-infected individuals clears the cell-free virus from circulation. Using the polymerase chain reaction (PCR), we were able to provide conclusive evidence that hyperimmune plasma is effective and maintains long-term neutralization of viremia. Using the cell test, we found that in most patients the total antibody level was maintained; in one of the ARC patients, it actually increased 8-fold and has remained at that level for nearly 2 years. The CD4+ cell count decreased in the AIDS patients but was stable in the ARC patient. Clinically, there was an initial improvement in all patients, but five of six of the advanced/terminal AIDS patients had died by month 17. Our studies suggest that passive immunization may be safe in ARC and AIDS patients. It reduces HIV-1 viremia to levels undetectable even by PCR. To advanced/terminal patients, the benefit is of limited duration, while to ARC patients it may be long-term. Therefore, passive immunization should start early in the disease.